Báo cáo tổng hợp, tiếp thu, giải trình ý kiến đóng góp về hồ sơ dự án Luật Công đoàn (sửa đổi) - Tổng Liên đoàn Lao động Việt Nam (2024)
Toàn văn Báo cáo tổng hợp, tiếp thu, giải trình ý kiến đóng góp về hồ sơ dự án Luật Công đoàn (sửa đổi).